Effect of leaves aqueous extract of Licania platypus (Hemsl.) Fritsch. On gastroprotection and gastrointestinal motility. - Orozco Aguilar, Josué (2018)
Licania platypus is a species widely distributed in tropical countries. Traditionally, it has been used in Central America for a variety of health problems, especially gastrointestinal problems. Aim: To investigate gastric antiulcer activity and gastrointestinal motility effect of Licania platypus leaves aqueous extract. Methods: Gastric lesions were induced by ethanol and indomethacin models; also other parameters were analyzed in pylorus-ligated model. Furthermore, was evaluated the effect on gastrointestinal motility phenol red. Results: Oral administration of aqueous extract (1000 mg/kg) significantly reduced the area of gastric lesions (p < 0,05) on both models. It was observed a significantly increased the gastric secretion volume and gastric mucus, whereas decreased total acidit and lipid peroxidation (p < 0,05). The aqueous extract of Licania platypus reduced the rate of gastric emptying (p < 0,05), but did not show any effect on intestinal transit. Conclusion: Licania platypus aqueous extract has a gastroprotective effect in different acute ulcer induction models and reducing the rate of gastric emptying. The activities proved in this study contribute ethnopharmacological toxicological knowledge attributed to Licania platypus.